THE KLINKER CEMENT IN THE PRODUCTION OF GAS FUEL FROM USE SPARINGLY (Conferencea, 2022)
Grow in ovens revolving cement used in the construction of agricultural enterprises is carried out. The size of rotary ovens klinker coming meyoriy the requirements of the higher of the firm, in the internal part of the oven to k free maturesopportunity to be able to in addition to the availability of the most comfortable, grounded in the structure of a combination of clay be difficult due to lack of expansion in the process of cooking, stick to one material as there are gaps [1-7]. These set the oven to eliminate deficiencies and installation, gas, fuel efficient, economical to use the main aims to need attention.